Globalization, the State and the Environment: Exploring the Limits and Options of State Activity - Marsden, Terry (The International Journal of Sociology of Agriculture and Food, 2021)
The paper explores the relationships between globalization and the state with reference to three interlinked aspects of environmental concern (agriculture-environmental relationships, environmental planning and policy and retailer regulation and food quality). New models of regulation emerge which suggest both a more variable and contingent conceptualization of the state is necessary. Social empowerment and the transposition of power with particular private economic sectors means that we must be more concerned with the substantial socio-political content of state power relations, rather than ascribing singular or coherent roles to the institutional matrix which traditionally defines 'the state.'